2022
DOI: 10.1039/d2sm00009a
|View full text |Cite
|
Sign up to set email alerts
|

Emerging modulators for osteogenic differentiation: a combination of chemical and topographical cues for bone microenvironment engineering

Abstract: Bone tissue engineering has primarily aimed to recreate the bone microenvironment by delivering key biomolecules and/or by modification of scaffolds to guide cell fate towards the osteogenic lineage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 86 publications
0
9
0
Order By: Relevance
“…[ 49 ] This preference could be associated with the similarity of this topography to the fibrillar organization of ECM, particularly collagen fibrils. [ 50 ] In addition, MSC differentiation may explain the plateau in cellular metabolic activity, which may be associated with a late stage of differentiation. [ 51 ] Altogether, these results revealed the potential of these PL microparticles as suitable platforms for cell differentiation in bone‐like cells.…”
Section: Resultsmentioning
confidence: 99%
“…[ 49 ] This preference could be associated with the similarity of this topography to the fibrillar organization of ECM, particularly collagen fibrils. [ 50 ] In addition, MSC differentiation may explain the plateau in cellular metabolic activity, which may be associated with a late stage of differentiation. [ 51 ] Altogether, these results revealed the potential of these PL microparticles as suitable platforms for cell differentiation in bone‐like cells.…”
Section: Resultsmentioning
confidence: 99%
“…[10,48,[62][63][64][65] Biochemical cues can be included using cells growth factors, chemical reagents, cellular proteins, kinases, small molecules, and synthetic materials, [66,67] whereas biomechanical stimulations involve surface properties of substrates, stiffness, roughness, pore size, topography, matrix hardness, external stress and strain, hydrostatic pressure, and electromagnetic field. [67][68][69] Synergistic stimulation of biochemical and biophysical cues leads to more precise simulation of microenvironments in vivo and a broader control over cell behaviors. [67] In one work, it was shown that the combining effect of fluid shear stress and presence of bone-like extracellular matrix synergistically enhanced the osteogenic differentiation of rat MSCs.…”
Section: Evaluation Of Mineralization and Osteogenic Markers Expressionmentioning
confidence: 99%
“…Previous studies have shown that the osteoconductive behavior of HA in collagen or gelatin-derived scaffolds potentiates cell differentiation. [30,33,34] Our data demonstrate the potential of both systems for autonomously guiding BM-hMSCs differentiation toward an osteogenic lineage, highlighted by the expression of membrane markers associated with osteogenic differentiation (BMP2, Col-I, OPN, and OCN). [30] However, the results also indicated that the GH+GD system underwent a faster differentiation process than the GH system, as observed by evident changes in BM-hMSCs behavior on day 14.…”
Section: Discussionmentioning
confidence: 62%
“…Previous studies have shown that the osteoconductive behavior of HA in collagen or gelatin‐derived scaffolds potentiates cell differentiation. [ 30,33,34 ]…”
Section: Discussionmentioning
confidence: 99%